Meta Analysis: Relationships of Risk Factors of Physical Activity and Obesity with Premenstrual Syndrome - Husna, Erza; Murti, Bhisma; Adriani, Rita Benya (Indonesian Journal of Medicine, 2022)
Background: Premenstrual syndrome is actually experienced by almost all women wherever they are, but most teenagers think the symptoms they feel do not require further intervention or treatment. This study aims to analyze the relationship between physical activity and obesity with premenstrual syndrome based on the results of several previous similar primary studies.Subjects and Method: This study was conducted using a meta-analysis study with PICO as follows: P= women aged 17-50 years, I= high physical activity and obesity, C= low physical activity and not obesity, O= premenstrual syndrome. Article searches were conducted using electronic databases, namely Pubmed, Google Scholar, Springer Link, Clinical Key, and Proquest. Article searches were conducted using keywords and the Mesh method as follows "physical activity and obesity and premenstrual syndrome", "physical activity and obesity and premenstrual syndrome and adjusted Odds Ratio", "physical activity and obesity and premenstrual syndrome and study cross sectional", " physical activity or obesity or premenstrual syndrome", "physical activity or obesity or premenstrual syndrome or adjusted odds ratio", "physical activity or obesity or premenstrual syndrome or study cross sectional". Articles were analyzed using the Review Manager 5.3 application.Results There are 13 articles from the continents of Africa, Asia, South America, and Europe which include Japan, Palestine, Arabia, Iran, Lebanon, Egypt, Brazil, and Turkey from 2000-2022 which were analyzed using PRISMA flow diagrams. Research studies show that women who do a lot of physical activity have a risk of developing premenstrual syndrome as much as 0.80 times compared to women who do less physical activity (aOR= 0.80; 95% CI = 0.51 to 1.25; p<0.001 ); and obese women had 1.03 times the risk of developing premenstrual syndrome compared with non-obese women (aOR = 1.03; 95% CI = 0.95 to 1.11; p = 0.49).Conclusion: Physical activity can reduce the risk of premenstrual syndrome and obesity can increase the risk of premenstrual syndrome.Keywords: physical activity, obesity, premenstrual syndromeCorrespondence: Erza Husna. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java, Indonesia. Email: erza.husna@gmail.com. Mobile: +6285747580999.Indonesian Journal of Medicine (2022), 07(02): 219-231https://doi.org/10.26911/theijmed.2022.07.02.10